Nitrite Reduces Ischemia-Induced Ventricular Arrhythmias by Attenuating Connexin 43 Dephosphorylation in Rats. (February 2016) - Maruyama, Daisuke; Hirata, Naoyuki; Tokinaga, Yasuyuki; Kawaguchi, Ryoichi; Yamakage, Michiaki
Abstract : BACKGROUND: Ventricular arrhythmias induced by ischemic heart disease are the main cause of sudden cardiac death. Ischemia can cause life-threatening arrhythmias by modulating connexin 43 (Cx43), a principal cardiac gap junction channel protein. The present study investigates whether nitrite can attenuate ischemia-induced ventricular arrhythmias and dephosphorylation of Cx43 in a rat model. METHODS: Rats were medicated with normal saline (control, n = 10), nitrite (0.015, 0.15, and 1.5 mg/kg, n = 9 or 10 each), and 0.15 mg/kg nitrite with either the nitric oxide scavenger 2-(4-carboxyphenyl)-4, 4, 5, 5-tetramethylimidazoline-1-oxyl-3-oxide, sodium salt (cPTIO; n = 9) or allopurinol (xanthine oxidoreductase inhibitor, n = 9). We determined the severity of ventricular arrhythmias based on arrhythmia scores and levels of phosphorylated Cx43. RESULTS: The median arrhythmia score may have been lower in the group given 0.15 mg/kg nitrite (4 [interquartile range IQR, 4–5]) than that in the control group (7.5 [IQR, 5.25–8]; P = 0.013). There was no difference among the control, the given 0.015 mg/kg nitrite (7 [IQR, 5–8]), and 1.5 mg/kg nitrite (7 [IQR, 5.5–7.75]; P = 0.95). The arrhythmia scores in the cPTIO (6 [IQR, 5–8]; P = 0.030) and allopurinol (7 [IQR, 5–8]; P = 0.005) groups may have been higher than that in 0.15 mg/kg nitrite group. Immunoblotting revealed that the level of phosphorylated Cx43 in the group given 0.15 mg/kg nitrite, but not in the other treated groups, was significantly higher compared with the control group ( P = 0.007). CONCLUSIONS: Nitrite may have attenuated acute ischemia-induced ventricular arrhythmias and Cx43 dephosphorylation in rats. Nitric oxide, which might be generated by xanthine oxidoreductase via nitrite reduction, appears to play a crucial role in this antiarrhythmic effect. Abstract : Published ahead of print October 29, 2015